THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL TYPE OF TEAMS GAMES TOURNAMENT WITH TYPE OF COURSE REVIEW HORAY TOWARD MATHEMATICS LEARNING OUTCOME OF THE STUDENTS OF SMP PUNDONG - Zulfi Jalal Muhsin; Abdul Taram (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
This research was conducted because students' mathematics learning outcomes were lack, the students had an opinion that mathematic was difficult and unpleasant, less active especially cooperation in learning, students perform other activities beyond teaching and learning strategies that teachers use less varied. This research is intended to find out the effectiveness of using cooperative learning model type Teams Games Tournament (TGT) with type Course Review Horay (CRH) Toward The Mathematics Learning Outcome of the VIII Grade Students of SMP Muhammadiyah 1 Pundong In The First Semester of Academic Year 2016/2017. The population in this research were all the students of grade VIII students of SMP Muhammadiyah 1 Pundong in academic year 2016/2017 consist of six classes, VIII A, VIII B, VIII C, and VIII D. Samples were taken three classes using purposive sampling techniques, it is obtained class VIII B as an experimental class I, class VIII D as an experimental class II and class VIII C as a control class. The data analysis technique that is used to test the prerequisites including normality test with Chi-Square formula, homogeneity test with Bartlet formula, and test hypotheses including F test and Least Significant Different (LSD). The result of the significant level of 5% and db = (2,56) showed (1) there is a difference in the results of students’ learning mathematics that is taught by cooperative learning model type Teams Games Tournament, cooperative learning model type Course Review Horay and direct instruction learning model. It is evidenced by the value    and Ftable , as a result , so,  rejected, and (2) cooperative learning model type Teams Games Tournament and cooperative learning model type Course Review Horay are more effective than direct instruction learning model on students’ mathematics learning outcomes. It is shown with the LSD test with a significant level of 5% and 56 degrees of freedom obtained in the first case because and LSD , as a result  so,  is accepted and means that . In case II  and LSD = , as a result  so  is rejected. Because  and , as a result  means . Meanwhile in case III  and LSD = , as a result  so rejected. Because  and , as a result  means . It can be concluded that .